Clinical Evaluation of Angamardaprashamana Mahakashaya and Kativasti in the Management of Lumbar Spondylosis (Katigraha) (AYUSHDHARA, 2022)
Lumbar spondylosis is a degenerative disease where degeneration occurs in lumbar vertebrae, intervertebral disc and in intervertebral joints, characterized by loss of hydration of disc followed by formation of osteophytes and transdiscal bridging. It involves the entire joint including the nearby muscles, underlying bone, ligament, disk and give rise to symptoms of Lumbar spondylosis. Katigraha is a Vataja nanatatmaja vyadhi mentioned by Sharangadhar and Shodala. As per Acharya Shodala, Vata situated in Asthi of Kati region, increased due to various Nidana (causes) and produce symptoms of vitiated Vata as Shula (pain), Pangutwa (disability) both the lower limbs known as Katigraha. Hence for treatment of lumbar spondylosis is correlated and treatment given according to Chikitsa modalities of Katigraha (Vatavyadhi Chikitsa). To evaluate the efficacy of Angamardaprashamana Mahakashaya and Kativasti in the management of lumbar spondylosis clinically a open, random, clinical trial is carried out on 100 patients in one group, as intervention Angamardaprashamana Mahakashaya Churna (powder form) is given orally and Kativasti (a type of sudation therapy) on lumbar region is given externally. Follow up taken in every 20th day upto 60 days. After treatment for statistical analysis of data paired t test is done and data shows highly significant result and shows remarkable changes in signs and symptoms. But its result of radiological changes are found not significant statistically. The relief % is analysis by using Oswestry Disability Index which shows 91% respond to treatment and 74% got major improvements. Thus, the study says that trial drug and therapy have capacity to improve lumbar spondylosis (Katigraha) significantly